Department of Pre-University Education, KarnatakaPUC Karnataka Science Class 11
Advertisement Remove all ads

If Y Sin ϕ = X Sin (2θ + ϕ), Prove that (X + Y) Cot (θ + ϕ) = (Y − X) Cot θ. - Mathematics

Sum

If y sin ϕ = x sin (2θ + ϕ), prove that (x + y) cot (θ + ϕ) = (y − x) cot θ.

 
Advertisement Remove all ads

Solution

Given:
y sin ϕ = x sin (2θ + ϕ)

\[\Rightarrow \frac{y}{x} = \frac{\sin\left( 2\theta + \phi \right)}{\sin\phi}\]

Applying componendo and dividendo: 

\[ \Rightarrow \frac{y - x}{y + x} = \frac{\sin\left( 2\theta + \phi \right) - \sin\phi}{\sin\left( 2\theta + \phi \right) + \sin\phi}\]

\[ \Rightarrow \frac{y - x}{y + x} = \frac{2\sin\left( \frac{2\theta + \phi - \phi}{2} \right)\cos\left( \frac{2\theta + \phi + \phi}{2} \right)}{2\sin\left( \frac{2\theta + \phi + \phi}{2} \right)\cos\left( \frac{2\theta + \phi - \phi}{2} \right)}\]

\[ \Rightarrow \frac{y - x}{y + x} = \frac{2\sin \theta \cos\left( \theta + \phi \right)}{2\sin\left( \theta + \phi \right) \cos \theta}\]

\[ \Rightarrow \frac{y - x}{y + x} = \frac{\sin \theta \cos\left( \theta + \phi \right)}{\sin\left( \theta + \phi \right) \cos \theta}\]

\[ \Rightarrow \frac{y - x}{y + x} = \frac{\cot \left( \theta + \phi \right)}{\cot \theta}\]

\[ \Rightarrow \left( y - x \right) cot\theta = \left( y + x \right) cot\left( \theta + \phi \right)\]

Concept: Transformation Formulae
  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

RD Sharma Class 11 Mathematics Textbook
Chapter 8 Transformation formulae
Exercise 8.2 | Q 16 | Page 19
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×